Strategy for the Use of Erythropoetin Alpha to Maintain Hemoglobin Level in Breast Cancer Patient Treated with Anthracycline-base of Adjuvant Chemotherapy - Achmad, Dimyati; Hariady, Yusuf Hariady; Isakh, Benny; Abdurrahman, Maman; Faried, Ahmad (International Journal of Integrated Health Sciences, 2013)
Objective: To evaluate the value of erythropoietin alpha (epoetin) administration, as an alternative treatment of anemia in the operable breast cancer patients.Methods: This is a multicenter phase III randomized clinical trial to evaluate the value of epoetin administration among anemic breast cancer patients who are undergoing anthracyclin-based adjuvant chemotherapy. Sixty four patients were incuded in this trial with initial hemoglobin (Hb) level of 10–12 g/dL. The patients were randomly distributed into two groups: one group received aministration of 40,000 IU epoetin/week for six times a week after operation and the other did not.  In the third week after the operation, both groups were started on a 6 cycles of adjuvant chemotherapy with three weeks intervals. Hb levels were evaluated during every chemotherapy cycle. Results: The Hb levels in the epoetin group were always above 10 g/dL up until the end of the sixth chemotherapy cycle or until the twenty first week post operation without blood transfusion. Conclusions: The administration of epoetin 3 weeks prior and 3 weeks after the first cycles of chemotherapy, maintains a sufficient/normal Hb level in breast cancer patients receiving anthracycline-based chemotherapy.Keywords: Anthracyclin-based chemotherapy, breast cancer, erythropoietin alpha DOI: 10.15850/ijihs.v1n1.102